Ekspresi inducible Nitric Oxide Synthase (iNOS) dalam Ginjal Ikan Mas (Cyprinus carpio. L) Setelah Paparan Linear Alkylbenzene Sulfonat (LAS) - Borut, Ruku (Indonesian Journal of Chemical Research, 2016)
This study aims to determine the expression of iNOS in renal tissue of carp to contamination LAS (linear alkyl benzene sulfonate). The method used in this study is an experimental method using laboratory based study of molecular exploration. The experimental design used was completely randomized design (CRD), with exposure treatment LAS namely (A) 0.01 mg / L, (B) 0.02 mg / L, (C) 0.03 mg / L, (D) 0.04 mg / L, (E) 0.05 mg / L and control (without LAS). The parameters measured were the expression of inducible nitric oxide synthase (iNOS) in renal tissue cranial carp after 96 hours of exposure to LAS. Detection of iNOS in renal tissue cranial carp do with immunohistochemical methods. T-test results showed that iNOS expression in the kidney tissue cranial carp at each treatment LAS exposure was significantly higher (P <0.05) than controls. The mean value of iNOS expression in control cells was 6.25%, a 14.5% cell treatment, treatment and 21% of the cells, the cells C treatment 32.5%, 36.5% D treatment of cells, and treatment E 28.25% cell.